An Investigation of the Convergence of PRC GAAP with IFRS - WANG, NAN (2006)
This research examines the development of international accounting convergence, and focus on the convergence of Generally Accepted Accounting Principles in China (PRC GAAP) with International Financial Reporting Standards (IFRSs). It analyzes the disparities between PRC GAAP and IFRSs by investigating the reported profits under the two sets of accounting standards during 2001-2005. It demonstrated how the PRC GAAP is differ from IFRSs and how firms' size, location and whether listed on overseas stock market influence the level of convergence in China by using a regression analysis. Moreover, it critically explained five factors in accounting standards that contribute most to the differences. Evidences show that on average IFRSs produce higher profits than PRC GAAP for the past five years. Further, although differences between the two sets of profits are increasing, the differences growth rates are declining after several accounting reforms in China towards the IFRSs. Five key factors in accounting standards have been found to explain the disparities in practices. We expect that this research would help to improve the PRC GAAP better converge with IFRSs in the future.